2021
DOI: 10.1002/ece3.7407
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome composition and degradation enzymes activity of black Amur bream (Megalobrama terminalis) in response to breeding migratory behavior

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…It is well established that microbiota play essential roles in host nutrition, physiology, and health [6,9]. However, little is known about the composition, diversity, and function of the microbiota associated with different environmental compartments and habitats in juvenile A. schlegelii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that microbiota play essential roles in host nutrition, physiology, and health [6,9]. However, little is known about the composition, diversity, and function of the microbiota associated with different environmental compartments and habitats in juvenile A. schlegelii.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota have been shown to affect the metabolic capacity of the fish host and to have beneficial effects on host nutrition, growth, reproduction, and health [5][6][7][8][9][10][11]. Hence, studies have increasingly focused on exploring the fish-gut microbiome, with the long-term goal of developing healthy and sustainable aquaculture production systems [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have established that fish gut microbial community compositions are distinct among different species, even among those co-habiting in the same environment ( Eichmiller et al, 2016 ; Baldo et al, 2017 ). Differentiation of the fish gut microbiome can frequently be predicted by host variable exogenous diet, environmental conditions, and phylogeny ( Fishelson et al, 1985 ; Su et al, 2020 ; Liu et al, 2021 ). In this study, we preliminarily investigated the relationship between cyprinid fish hosts CO1 genetic distance and gut microbiome dissimilarity.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed Proteobacteria and Firmicutes phyla as typical dominant flora in the gut of the four fish species. Proteobacteria and Firmicutes are two phyla typical dominant flora in the intestine of many fish, such as Oncorhynchus mykiss (Ingerslev et al, 2014), Nibea coibor and Nibea diacanthus (Li et al, 2019), Megalobrama terminalis (Liu et al, 2021), Micropterus salmoides (Zhou et al, 2021) andSymphysodon haraldi (Zhang et al, 2021). The four fish species had variations in abundant of microbiota species.…”
Section: Discussionmentioning
confidence: 99%
“…The intestine tract is the main site for digestion and nutritional uptake, which has been regarded as a key organ in fish nutrition (Kumar et al, 2005;Wang et al, 2018;Zhou et al, 2021). The fish digestive enzymes activities are closely related to the diet consumed and the ability of fish to digest and absorb different nutrients (Bakke et al, 2010;Liu et al, 2021). Evidently, previous studies found herbivorous fish such as Roho labeo (Labeo rohita ) and Japanese eel (Anguilla japonica ) had stronger amylase activity compared to carnivorous fish such as Great white catfish (Wallago attu ) (Agrawal et al, 1975) and rainbow trout (Oncorhynchus mykiss ) (Hidalgo et al, 1999).…”
mentioning
confidence: 99%